Study of stability conditions of stochastic disturbed systems with delay - Nechaeva , I. N.; Khusainov , D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Linear stochastic differential systems with a single lag are considered. Sufficient conditions for uniform (in lag) stability in the mean-square under constantly acting perturbations are obtained.